CFD Modeling of a Supersonic Top Blown Lance in a CAS‐OB Process: Development of Gas Heat and Mass Transfer Correlation. Issue 11 (10th February 2015) - Kärnä, Aki; Järvinen, Mika P.; Fabritius, Timo
Abstract : While many metallurgical processes involve the use of top lances, little is known about the heat and mass transfer coefficients of such instruments due to difficulties in measurement procedures. This paper presents a new gas heat and mass transfer coefficient model which can be implemented as part of a CAS‐OB process model. We begin by testing several turbulence models against the data provided in the literature, in order to identify a model suitable for the supersonic jet CFD model. We then further test the resulting modeling setup using jet impingement measurement data. Following the successful validation of this CFD setup, we use the setup to simulate several cases of real lance conditions under a CAS‐OB bell refractory. Based on these simulations, we calculate the overall heat and mass transfer coefficients and develop heat and mass transfer correlations for a CAS‐OB lance. Abstract : A series of CFD simulations are created to determine heat and mass transfer coefficients for supersonic impinging jet in the CAS‐OB process. The flow model is first adjusted and validated with available experimental data. The resulting correlations are important in calculating chemical reactions in process modeling software.